The zombie generation. The excessive use of cell phones in university classrooms in Peru. - Montenegro Ordoñez, Juan (2023)
Objective: to describe the knowledge of university students about the effects on learning and health of excessive use of cell phones in classrooms. Methodology: descriptive and explanatory. The sample was   made up of 207 students: 59 men and 148 women; administered instruments were applied. Results: Regarding learning, health and the use of cell phones in the classroom, 66% of students agree that the use of cell phones in the classroom affects learning; 44% would support banning cell phone use in classrooms. 68.6% recognize the teacher's authority to prohibit their use in the classroom, and 49.8% support the idea of creating a space to store students' cell phones during class. Conclusion: university students know that excessive cell phone use affects the physical and psychological health of users, and even the nervous system, generates addiction, affects human interaction, affects learning, because it distracts and distances attention from achievement. of the expected learning.